Human resource development practices as a strategy in improving executives retention in oil palm organizations - Taib, Anita (Panoply Consultancy, 2017)
The purpose of this article is to explore the Human Resource Development (HRD) practices and factors that influence executives' retention as well as uncovering strategies in retaining them in selected oil palm organizations. This article is based on a review of the HRD literature particularly in talent retention. Human resources are very important asset in any organization and act as a source of competitive advantage in the organization. Many studies have focused on the factors that contribute to the employee retention from the Human Resource Management (HRM) practices perspective, whereas, this study will look into it from the perspective of HRD. The differences between HRD and HRM in terms of meaning and practices are discussed to give a clearer picture of both fields and how they are linked to one another so as to identify the factors and the appropriate strategies to retain executives.